Assembly Training, Software Installation and Computer Troubleshooting at Karang Putih Community Learning Activity Center - Mumuh Muharram; Heru Dibyo Laksono; M. Irmansyah; Asri Astianingsih; Pinto Anugrah (Jurusan Teknik Elektro, Universitas Andalas, 2021)
This service activity will be focused on everything related to assembly, software installation and computer troubleshooting for participants in the Karang Putih Community Learning Center (PKBM). The activity steps are carried out in several stages, starting from field surveys, literature studies, discussions, to the implementation of training activities that use an approach between theory and practice. Indicators of the success of this activity are the Assembly Training, Software Installation and Computer Troubleshooting. This training is used by partners, by seeing that this training has been in accordance with the needs of the community in the partner environment; This training can help the educational process and skills in practice quickly; and this training can be conducted by other Community Learning Activity Centers (PKBM). The attention of the participants in this activity was quite large, almost all of them were active in the discussions and practices that were carried out. From this discussion and training it was revealed that about 75% of the participants had understood the material as a whole.